2020
DOI: 10.1021/acsenergylett.0c02159
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Versatile 3D Thermoelectric Generators by Additive Manufacturing

Abstract: Additive manufacturing (AM) is a recent growing technology, which is currently implemented for different application fields, from rapid prototyping to cost-effective manufacturing of industrial components with complex shapes. Printable thermoelectric materials offer synergies with AM and can be integrated into 3D printed thermoelectric generators (TEGs). In this work, we have formulated an Ag 2 Se-based n-type printable thermoelectric (TE) ink with a high figure-of-merit of ∼1 at room temperature. Three scaffo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 20 publications
0
48
0
Order By: Relevance
“…As an “electron crystal, phonon liquid” n-type material, silver selenide (Ag 2 Se) is environmentally friendly and abundant, with high electrical conductivity and low thermal conductivity at room temperature. It has become an ideal Bi 2 Te 3 replacement material and is the most promising n-type material in recent years [ 29 , 30 , 31 , 32 , 33 ]. Mallick et al initially prepared a flexible-folded TEG consisting of 13 thermocouples using screen printing with an output voltage of 181.4 mV at ΔT of 110 K, where Ag-Se ink was used as n-type leg and PEDOT:PSS as the p-type leg.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an “electron crystal, phonon liquid” n-type material, silver selenide (Ag 2 Se) is environmentally friendly and abundant, with high electrical conductivity and low thermal conductivity at room temperature. It has become an ideal Bi 2 Te 3 replacement material and is the most promising n-type material in recent years [ 29 , 30 , 31 , 32 , 33 ]. Mallick et al initially prepared a flexible-folded TEG consisting of 13 thermocouples using screen printing with an output voltage of 181.4 mV at ΔT of 110 K, where Ag-Se ink was used as n-type leg and PEDOT:PSS as the p-type leg.…”
Section: Introductionmentioning
confidence: 99%
“…Mallick et al initially prepared a flexible-folded TEG consisting of 13 thermocouples using screen printing with an output voltage of 181.4 mV at ΔT of 110 K, where Ag-Se ink was used as n-type leg and PEDOT:PSS as the p-type leg. Later on, Ag-Se ink was applied to 3D printing, three shapes of samples were prepared, and the output voltage was 55 mV at 70 K [ 29 , 30 , 31 ]. To obtain n-type flexible thermoelectric devices with better performance, some researches have been conducted on composite organic and inorganic materials to make them flexible and to improve the thermoelectric properties of the composites [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cu 2 Se has been shown to be spin coated, [83] Ag 2 Se to be printed, [84][85][86] and SnSe to be 3D printed. [36] Thermoelectric properties of these printed selenides are represented in Figure 12 (also Table S6, Supporting Information), along with images of the printed materials and schematics of manufacturing techniques.…”
Section: Selenidesmentioning
confidence: 99%
“…Many studies have reported inorganic TE slurries/powders that can be printed by SLM/SLS, 43,45,46 DIW [47][48][49] or stereolithography 50 to form ingots. Furthermore, the same materials can be formulated as inks, which can be directly painted onto 3D objects [51][52][53] or patterned on flexible substrates by inkjet printing, 42,54 aerosol jet printing, 53,55,56 dispensing, 57 or screen printing 52,[58][59][60][61][62][63][64] to form shape-conformable and flexible devices. However, the combination of those printing techniques with the search of morphological anisotropy to improve the final performance has been largely overlooked.…”
Section: Printed Anisotropic Inorganic Thermoelectric Materialsmentioning
confidence: 99%